Comparing health outcomes of care experienced children to children not in care in Scotland 2009-2016. (20th October 2021) - Allik, M; Brown, D; Leyland, AH; Henderson, M
Abstract: Background: Internationally, there is little quantitative evidence on how the health of children who have experienced social care compares to children in the general population. Invariably, available evidence suggests that care experience is related to poorer health, but often this is based on small sample sizes or without comparison to children who have not been in care. The Children's Health in Care in Scotland (CHiCS) study provides the first Scotland-wide evidence on health outcomes of care experienced children (CEC) compared to children in the general population (CGP). Methods: We undertook an individual level administrative data linkage of social care, morbidity, prescribing, death and birth records from August 2009 to July 2016. The CEC cohort was defined as all school-age children who were in social care in 2009/2010 (n = 13, 831) and the CGP cohort includes school-age children who were not in care (n = 649, 771). Age-standardized rates per 1000 person-years were calculated for hospitalisation by cause, prescription types and cause of death for both cohorts. Results: Initial results show that CEC experienced higher average rates of mortality, prescriptions, and different types of hospitalisations during the study period (not adjusted). There are substantial differences in the types of prescriptions and reasons for hospital admission between the cohorts; CEC are more likely to be prescribed antidepressants (rate of 260.2 per 1000 person-years for CEC compared to 114.4 for GCP) and to attend psychiatric outpatient appointments (rate of 163.2 compared to 32.6). Care experienced young women have higher rates of medical abortions (rate of 11.3 compared to 6.1). Conclusions: The results from this study indicate that CEC are more likely to contact the health services, particularly for mental and sexual/reproductive health reasons, and these problems may track into adulthood. Interventions to reduce inequalities in health for CEC should focus on these areas. Key messages: CEC had higher rates of mortality, prescriptions, and hospitalisations during the study period. CEC are more likely to contact the health services for mental and sexual/reproductive health reasons.